Comparative Study of Japanese and Indonesian Panji Mask in Light on Fine Art Elements and Principles - Subiyantoro, Slamet; Fukuda, Takamasa; Hindrayani, Aniek; Fahrudin, Dimas; Kuswara, Yogi (Harmonia: Journal of Arts Research and Education, 2023)
Panji masks are one of the mask arts that originated in Indonesia and come in a variety of styles. One of the existing Panji mask styles is the Yogyakarta style, made of Pule wood and used in dance or theater performances. While in Japan, masks used in dance or theater performances, known as Noh masks, are made of cypress wood. Panji masks and Noh masks are long-standing cultural heritage arts. This study aims to identify and analyze the similarities and differences between the elements of art and the principles of art preserved in the Panji and Noh masks. A comparative qualitative method was used for the study. Library research, observation, interviews, documentation, and focused group discussions (FGD) were used to collect the data. Data processing and preparation, data reduction, data presentation, and conclusion drawing were all completed in stages. The results revealed similarities and differences between the Panji and Noh masks. Several principles are shared by Panji and Noh masks, including point elements, line shape, the principle of unity, balance, rhythm, proportion, and the principle of harmony. The line, field/shape element, color element, texture element, and emphasis principle are all different. These similarities and differences are due to a variety of factors, including the two countries’ geographical proximity (both on the Asian continent), as well as their history, customs, and culture.